Road pricing : technologies, economics and acceptability - Walker, John (IET transportation series, 2018)
Road pricing is increasingly being implemented around the world to combat congestion, curb carbon emissions, compensate for falling revenues from fuel duty, improve the efficiency of the existing transport infrastructure, and fund new transport projects. This book outlines some of the economic theory behind these schemes.